Standing Stock of Hampala macrolepidota in the Lubuk Siam Lake, Lubuk Siam Sub-District, Kampar District, Riau Province - Deby Ansah; Muhammad Fauzi; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTHampala macrolepidotacommonly inhabit the Lubuk Siam Lake. A research aims to understand the standing stock, relative growth rate and recruitment pattern of H. macrolepidota in that lake was conducted in March 2018. Fish was sampled everyday for a week period, in 3 sampling points (in the flow of water enter the lake, in the middle of the lake and at the end of the lake), using gill nets. The standing stock was analyzed using Leslie method, while the relative growth rate and recruitment were analyzed using FISAT II software. Result shown that the standing stock of the fish was 339 kg, (L∞316.05 mm), K 0.54/year and t0 -0.0141/year. Recruitment percentage in March was 6.33% and the highest predicted recuritment was in May (19.6%). Keywords: Leslie method, Recruitment, Growth rate, Hampala barb